Deep Learning in a Futuristic Pedagogical Review: A Critical Paradigm for 21st Century Learning - Karmilah, Lilah; Margo, Dede (International Conference on Elementary Education, 2025)
The transformation of 21st-century education demands a deeper, more reflective, and meaningful approach to learning, especially in the face of the complexity of the digital age and the crisis of values. Deep learning is one of the key concepts in futuristic pedagogy, which emphasizes conceptual understanding, value integration, and critical thinking skills. This study aims to examine deep learning from a critical pedagogical perspective as a transformative learning paradigm relevant to future challenges. The methodology used is a literature study, reviewing various national and international scientific sources related to deep learning, futuristic pedagogy, critical pedagogy, and 21st-century learning. The results of the study show that deep learning is in line with the principles of critical pedagogy, as both emphasize the active role of learners in the learning process, reflective awareness, and orientation towards social change. The conclusion of this study confirms the importance of integrating deep learning into the curriculum and learning practices as part of a vision of future education that is not only adaptive but also liberating and civilized.